Iconology Analysis in Advertising Design, Case Study Go-Jek Billboard Advertising: Series "Mager Tanpa Laper" in Yogyakarta-Indonesia - Arif Ardy Wibowo; Peter Ardhianto (International Journal of Visual and Performing Arts, 2020)
Billboard is one of the outdoor media that still has a vital role in the world of advertising despite being in the digital age. Billboard advertising is still used by a large number of companies to promote their products or services. One of them is Go-Jek Indonesia's online transportation company. This research will discuss the concept of the Go-Jek billboard advertisement, the Mager Tanpa Laper version in Yogyakarta. This study will use the iconographic and iconological approach offered by Erwin Panofsky. The method is then used to analyze the concept of Go-Jek advertising. The results of this study found that the advertising version of Go-Jek Mager Tanpa Laper brings an understanding that wants to be transferred to the target market in the form of ease and convenience in ordering food. Without the need to get out of the house and queue up - as evidenced by the tagline Mager Tanpa Laper (Lazy to Move), just Go-Jekin (use the Go-Jek Application).